General principles of the insurance law of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this paper, the author discussed the principles of insurance law, which are the basis to conduct insurance business in the Republic of Kazakhstan. Disclosed the principles of protection of property, the accumulation of public finances, reducing the risk of unexpected losses. There was also a system of principles of insurance activity. We used the works of foreign authors: Baysalov SB, DL Baideldinov As scientific works of scientists of the Russian Federation: Krokhina Y.A., Alekseev S.S., Smirnov M.B., Denisova I.P., Shikhov A.K .Key words: principles of insurance business, insurance law, insurance law.